Immediate postpartum cardiorespiratory collapse:a management quandary - Mohd Shah, Azarisman Shah; Roslani, Liza; Hassan, Radhiana; Saravanamuttu, S. Saujana; Oteh, Maskon; Mohd. A. , Rosli; Abdul Rani, Mohammed Fauzi (Lippincott Williams & Wilkins Ltd., 2010)
A 35-year-old multiparous woman was found unresponsive, tachypnoeic, hypoxic and in shock 4 h postpartum. The ECG revealed S1 Q3 T3, a right bundle branch block pattern and right-axis deviation. The computed tomography of her pulmonary arteries revealed bilateral pulmonary artery thrombosis with dilated right ventricle. She was fibrinolyzed with intravenous Tenecteplase 30mg bolus. Her saturation and tachypnoea improved and her ECG reverted to sinus rhythm subsequently. We discuss our use of off-label Tenecteplase in postpartum pulmonary embolism and review the literature. Blood Coagul Fibrinolysis 21:601–604 2010 Wolters Kluwer Health | Lippincott Williams & Wilkins.